2010
DOI: 10.1007/s10557-010-6227-y
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of TAK-491, a New Angiotensin Receptor Blocker, and Pioglitazone, in Reducing Myocardial Infarct Size

Abstract: TAK-491 and PIO independently limited myocardial IS in a dose-dependent fashion; and the effects were additive. The mechanism of protection and the role of TAK-491 in this clinical setting should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…Here, we show that both VA and AL augmented Akt phosphorylation at Ser-473 and Thr-308 after ischemia-reperfusion, and that the levels of P-Akt were highest in the AL50+Va16 group, in agreement with their smallest IS. Previously, we showed that azilsartan (TAK-491) reduced IS and increased Akt phosphorylation following ischemiareperfusion in non-diabetic rats [18]. Previous studies have also shown that ARBs increase Akt phosphorylation [27,[54][55][56] and several studies have shown that AL increases Akt phosphorylation in various experimental models [52,[57][58][59][60].…”
Section: Akt Phosphorylationmentioning
confidence: 95%
See 2 more Smart Citations
“…Here, we show that both VA and AL augmented Akt phosphorylation at Ser-473 and Thr-308 after ischemia-reperfusion, and that the levels of P-Akt were highest in the AL50+Va16 group, in agreement with their smallest IS. Previously, we showed that azilsartan (TAK-491) reduced IS and increased Akt phosphorylation following ischemiareperfusion in non-diabetic rats [18]. Previous studies have also shown that ARBs increase Akt phosphorylation [27,[54][55][56] and several studies have shown that AL increases Akt phosphorylation in various experimental models [52,[57][58][59][60].…”
Section: Akt Phosphorylationmentioning
confidence: 95%
“…eNOS phosphorylation eNOS is involved in the delayed form of ischemic preconditioning [62] and is essential for the IS-limiting effects of statins [63]. We have shown that azilsartan (TAK-491) increases myocardial calcium-dependent NOS activity and eNOS phosphorylation at Ser-1177 following ischemia-reperfusion in the rat [18]. Losartan also increases eNOS phosphorylation in the rat heart [64].…”
Section: Akt Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al (12) reported that 3-day pre-treatment with pioglitazone (2.5 mg/kg/d) increased ERK1/2 phosphorylation in rat heart. Another TZD, rosiglitazone, augments ERK1/2 activation in myocardium of hypercholesterolemic rabbits subjected to I/R injury (13).…”
Section: Introductionmentioning
confidence: 99%
“…There were several reports indicating the myocardial apoptosis in the EAM rats and ARBs can effectively prevent it due to their action on RAS. For instance, ARB can block the endoplamic reticulum stress and caspase12 activation in the EAM rats thus prevents cardiomyocyte apoptosis (Singh et al, 2008;Tsutsui et al, 2007;Ye et al, 2010;Matsusaka et al, 2006) (Figure 1). …”
Section: Arb and Cardiomyocyte Apoptosismentioning
confidence: 99%